Paper doll : notes from a late bloomer - Mulvaney, Dylan (Abrams Image, 2025)
In her memoir, Paper Doll, Dylan pulls back the curtain of her "it girl" lifestyle with an honest, witty, and intimate reflection of her life post-transitioning. She covers everything from her first big break in theater to the first time her dad recognized her as a girl to how she handled scandals, cancellations, and tucking. Dylan's humor and honesty is woven throughout this colorful memoir, uncovering a life beyond the 365 days that will delight her fans and create new ones alike.